A hospital-based cross-sectional study on health problems and the factors affecting the health of adolescent girls in rural population - P., Sreekavya; Channabasavanna N.; K. B. Mahendrappa; G. M. Kumar (International Journal of Contemporary Pediatrics, 2023)
Background: Many adolescent girls die prematurely due to various preventable or treatable reasons, and many more suffer from chronic ill-health and disability. The objective of this study was to assess the nutritional status, gynaecological problems, and psychological problems of adolescent girls attending the Paediatric OPD and ward. The aim was to study the prevalence of malnutrition in adolescent girls attending paediatric OPD and ward. Methods: A cross-sectional hospital-based study was conducted on adolescent girls attending Paediatric OPD and ward of Adichunchanagiri institute of medical sciences and research centre, B. G. Nagara from November 2019 to November 2020. A total of 374 adolescent girls (10-17 years) were enrolled. Clinical examination was done after recording their weight and height. Body Mass Index was computed. Results: Mean age of the study participants was 13.05 years, and majority of them were from low socioeconomic status. Around 41.2% of the fathers had semi-skilled jobs, and 19.3% of the mothers had clerical jobs, shop owners, or farmers. About 71.1% of the adolescents attained menarche with a mean age of 13.2 ± 0.11 years. 62% had normal BMI, followed by 25.1% with underweight, overweight in 9.4%, and obese in 3.5% of the adolescents. Around 62% of the adolescents were normally nourished, and 38% were malnourished. Conclusions: Socioeconomic status, occupation of mothers, family types and diet of the adolescents had a significant association with poor nutritional status. It is important to understand the need for evaluation of malnourished adolescent females and their causes to prevent chronic illness and death among them.